Efektivitas Penerapan Sanksi Pidana Bagi Mafia Tanah di Provinsi Lampung - Suta Ramadan; Atika Putri Jayanti; Aldi Yansah; Raudatul Zanah Al-Zahra (Hakim, 2024)
This study investigates crimes in property and object crimes, focusing on the "Land Mafia in Lampung Province" case which occurred in South Lampung. This research aims to (1) find out and analyze what causes land officials to help/commit legal violations, and (2) find out and analyze the applicable legal regulations. The type of research used in this research is empirical legal research. Data collection techniques using document study techniques, observation and interviews. The results of the research show that (1) Forms of misuse of land documents made by land officials are caused by the existence of positional power. Then the form of abuse is that land officials help to carry out unlawful acts. Then, if there has been an unlawful act that constitutes a criminal act, then the action is correct law enforcement so that individuals can change and realize that the actions they have committed are wrong.